Lacertus fibrosus release in proximal median nerve entrapment- a systematic review - Qutaiba N. M. Shah Mardan (20884597) (2025)
Background The role of lacertus fibrosis as the primary perpetrator behind the illusive pronator teres syndrome is becoming increasingly recognized in recent literature. The aim of this systematic review is to explore the outcomes of lacertus fibrosis release in patients complaining of proximal median nerve entrapment signs and symptoms. Methodology In this systematic review, Pubmed, Cochrane Library, Scopus, Ovid databases were reviewed. Studies in which structures, other than the lacertus fibrosus, in the proximal forearm had been concomitantly released were deemed illegible. Various outcome assessment tools were utilized; those were pain, numbness, and satisfaction visual analog scales, return of function and muscle strength, quick DASH, work DASH, and activity DASH scores. Adherence to PRISMA guidelines was maintained. Results A total of seven studies, three interventional and 4 retrospective observational studies, were included in this review out of 118 articles. These included 446 participants who underwent lacertus fibrosis release with a mean age of 45 years old across a mean duration of postoperative follow-up of 16.1 months. A significant proportion of the patients had a history of unsuccessful conservative or surgical management (prior carpal tunnel release in 10.5%). Minimal access surgery under WALANT was performed in 95%, US-guided release under WALANT in 3.3%, and open exploration was done in 1.5%. A horizontal incision hidden in the elbow flexion creese was done in 74.2%, oblique incision 2 cm distal and 2 cm radial to the medial epicondyle in 20.8%, and open exploration through a Z-shaped incision over the antecubital fossa in 1.5%. Immediate pain relief and return of function and strength was reported in 99.6%. A significant improvement was reported in postoperative quick DASH (mean = 24 points), work DASH (mean = 28.8 points), and activity DASH (mean = 44.8 points). Further, a significantly lower VAS score was obtained on pain, numbness, and paraesthesia scales. There were two complications, a case of postoperative haematoma and another case of surgical site infection. Seven patients complained of residual symptoms by the end of the follow up duration; carpal tunnel release was done in three and release of superficialis arcade was necessitated in four other cases. Conclusion Lacertus syndrome can be optimally managed by surgically releasing the lacertus fibrosus. This can be done as a minimally invasive procedure under WALANT. A high index of suspicion is required when encountering patients with signs and symptoms of median nerve entrapment, specifically those who were treated unsuccessfully with the presumption of carpal tunnel syndrome. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-025-06493-5